2022
DOI: 10.1038/s41598-022-04973-x
|View full text |Cite
|
Sign up to set email alerts
|

A panel of emerging EMT genes identified in malignant mesothelioma

Abstract: Malignant mesothelioma (MESO) is a highly aggressive cancer with poor prognosis. Epithelial–mesenchymal transition (EMT) is a critical process in malignancies involved in tumor angiogenesis, progression, invasion and metastasis, immunosuppressive microenvironment and therapy resistance. However, there is a lack of specific biomarkers to identify EMT in MESO. Biphasic MESO with dual phenotypes could be an optimal model to study EMT process. Using a powerful EMTome to investigate EMT gene signature, we identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The in-silico analysis revealed that several targets triggered by miRNA-181a-5p and 193a-5p were involved in mesothelioma development. In particular, we found proteins involved in the regulation of pathways aberrantly activated in mesothelioma, such as MAPK, PI3K-Akt and mTOR signalling pathways [ 4 , 11 , 12 ], as well as the EGFR [ 13 ], Hippo [ 14 , 15 ], epithelial to mesenchymal transition [ 16 ] and NF-kappa B signalling pathways [ 17 , 18 ]. While miRNA-181-5p exerts an inhibitor regulation on those pathways, thereby eliciting a tumor-suppressor effect, miRNA 193-5p had an inverse role.…”
Section: Resultsmentioning
confidence: 99%
“…The in-silico analysis revealed that several targets triggered by miRNA-181a-5p and 193a-5p were involved in mesothelioma development. In particular, we found proteins involved in the regulation of pathways aberrantly activated in mesothelioma, such as MAPK, PI3K-Akt and mTOR signalling pathways [ 4 , 11 , 12 ], as well as the EGFR [ 13 ], Hippo [ 14 , 15 ], epithelial to mesenchymal transition [ 16 ] and NF-kappa B signalling pathways [ 17 , 18 ]. While miRNA-181-5p exerts an inhibitor regulation on those pathways, thereby eliciting a tumor-suppressor effect, miRNA 193-5p had an inverse role.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the function of integrins is not limited to simple mechanical cell adhesion but also influences cell proliferation and other processes by transmitting signals in both directions through the cell membrane [15]. The association between malignant mesothelioma and IT- GAV is primarily unexplored, with the existing reports on ITGAV addressing the genes associated with wound healing and EMT [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] SPARC expression in tumor-associated stroma is instrumental in tumor survival and progression and serves as a prognostic factor. 14,15,17 In mesothelioma, SPARC is linked to epithelial-mesenchymal transition, 18 and both its expression in tumor stromal cells and blood SPARC levels correlate with prognosis. 19,20 In the current study, SPARC was found to be positive in mesothelioma cells and negative in lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%